Antitrust Issues in Intellectual Property Law, Second Edition - Lyerla, Bradford P (American Bar Association, 2024)
The intersection of intellectual property law and antitrust law is busy and complicated, and there's no reason to believe that the heavy traffic will abate anytime soon. In the past year alone, the congress, regulators and courts have all made significant statements affecting the historical balance between the competing policies underlying intellectual property and antitrust law.Antitrust Issues in Intellectual Property Law, Second Editionfocuses on recent developments, helping the IP practitioner stay informed about the law and the many ways in which antitrust law limits, disciplines, and counterbalances intellectual property law and vice versa. Topics cover antitrust issues in these key areas of intellectual property law:Acquisition, procurement, and ownershipLicensingLitigationSettlements under the Hatch-Waxman ActIncorporation of IP into a standard set by a standard-setting organization (SSO)